2018
DOI: 10.3390/mi9120611
|View full text |Cite
|
Sign up to set email alerts
|

Localized Deformation and Fracture Behaviors in InP Single Crystals by Indentation

Abstract: The indentation-induced deformation mechanisms in InP(100) single crystals were investigated by using nanoindentation and cross-sectional transmission electron microscopy (XTEM) techniques. The results indicated that there were multiple “pop-in” events randomly distributed in the loading curves, which were conceived to arise primarily from the dislocation nucleation and propagation activities. An energetic estimation on the number of nanoindentation-induced dislocations associated with pop-in effects is discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][18][19][20][21][22][23][24][25][26][27]. С его помощью исследуются ионные и ковалентные монокристаллы (KCl, LiF, Si, InP) [2,[4][5][6][7]9,10,21], металлы (Al, Cu, W) [18,19], оксиды (ZnO, MgO, SiO 2 , Al 2 O 3 , B 6 O, SrTiO 3 ) [19,24], твердые и свехтвердые соединения [19], молекулярные кристаллы [25], тонкие пленки [23], полимеры [26], стекла [27] и др. Этот небольшой перечень материалов, исследуемых с помощью наноиндентирования, наглядно демонстрирует степень его применения специалистами, занимающихся вопросами физики прочности и пластичности и физического материаловедения.…”
Section: Introductionunclassified
“…[2][3][4][5][6][7][8][9][10][18][19][20][21][22][23][24][25][26][27]. С его помощью исследуются ионные и ковалентные монокристаллы (KCl, LiF, Si, InP) [2,[4][5][6][7]9,10,21], металлы (Al, Cu, W) [18,19], оксиды (ZnO, MgO, SiO 2 , Al 2 O 3 , B 6 O, SrTiO 3 ) [19,24], твердые и свехтвердые соединения [19], молекулярные кристаллы [25], тонкие пленки [23], полимеры [26], стекла [27] и др. Этот небольшой перечень материалов, исследуемых с помощью наноиндентирования, наглядно демонстрирует степень его применения специалистами, занимающихся вопросами физики прочности и пластичности и физического материаловедения.…”
Section: Introductionunclassified
“…The Young’s modulus and hardness are of the greatest interest, because they reflect the elastic deformation and resistance to permanent deformation. Nanoindentation is regarded as a good method to study the mechanical property of materials at the nanoscale level, including various nanostructures [20,21] and thin films [22,23,24,25,26,27,28,29,30,31,32]. G. Han et al reported the enhanced nanomechanical properties of FTO thin films through the modification of the structure-morphology via the post-annealing process [15].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, it has been also interpreted as the manifestations of the dislocation activity [18,19,20] depending strongly on the crystal structure of the test materials [25], temperature [26], the shape of indenter tip [27] and indenter angle [28]. Furthermore, the correlations between pop-in behaviors and dislocation activities of materials have been widely studied by combining microstructural observations with the cross-sectional transmission electron microscopy in recent years [29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…For the nanoindentation responses, the single “pop-in” behavior is often observed in the zincblende-structured, such as GaAs and InP single-crystals [31,32]. Whereas the multiple “pop-ins” has been ubiquitously identified in the hexagonal-structured materials, such as GaN thin films [33] and ZnO single-crystal [29].…”
Section: Introductionmentioning
confidence: 99%